PENERAPAN METODE PEMBELAJARAN FLASH CARD DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMP NEGERI 11 MAKASSAR - Nur Hanifah Hamzah; Mustamin; Syarifah Raehana; Akhmad Syahid; Andi Hasriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the increase in student learning motivation through the application of the Flash Card learning method in the subjects of Islamic Religious Education (PAI) and Character Building in class VIII.C SMP Negeri 11 Makassar. This study uses Classroom Action Research (CAR) with the John Elliot model which is implemented in two cycles. Each cycle includes the stages of planning, action implementation, observation, and reflection. The research subjects numbered 28 students consisting of 13 boys and 15 girls. Data collection techniques used observation, interviews, documentation, and a learning motivation assessment rubric. Data were analyzed quantitatively through calculating the average and percentage of learning motivation, and qualitatively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the Flash Card learning method is able to increase student learning motivation. This increase is seen from the increasing activity of students in participating in learning, increasing attention to teacher explanations, courage to express opinions, active discussions, enthusiasm for completing assignments, and enthusiasm in participating in learning. In addition, the learning atmosphere becomes more interesting, interactive, and student-centered compared to learning using the lecture method. The learning improvements implemented in each cycle also had a positive impact on student engagement during the learning process. Thus, the Flash Card learning method has proven effective in increasing student motivation in Islamic Religious Education and Character Education in class VIII.C of SMP Negeri 11 Makassar. Therefore, this method can be used as an alternative, innovative learning strategy to create a more active, enjoyable, and meaningful learning process.